PENERAPAN KEEFEKTIFAN BAHAN AJAR BERBASIS MODEL PROBLEM SOLVING PADA SUB MATERI POKOK REAKSI REDOKS TERHADAP HASIL BELAJAR SISWA KELAS X DI SMA NEGERI BANJARMASIN - Hana Yuliana; Muhammad Kusasi; Iriani Bakti (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2015)
Abstract. Has done research on the effectiveness of the application of model-based teaching materials on problem solving sub subject matter of redox reactions. This study aims to (1) determine differences in cognitive achievement between students with learning students with conventional and model-based learning teaching materials problem solving, (2) determine differences in the activity of students, between students and students with learning and conventional learning models of problem-based teaching materials solving, (3) determine students' response to the model-based learning teaching materials problem solving. This research method is a quasi-experiment. Samples were students of class X-3 and X-5 SMAN 12 totaling 44 people, class X-1 and X-2 SMAN 4 amounted to 74 people as well as the class X-1 and X-3 SMAN 2 Banjarmasin numbered 76 people. The research design used was a nonequivalent pretest-posttest control group design. Collecting data using tests of student learning outcomes, student activities and questionnaire responses. Data analysis using t-test with a significance level of 5%. Techniques used for the activity and the percentage of response analysis. Calculation of the t-test showed that t > t table therefore concluded that there is a significant difference in learning outcomes yng between the experimental and control classes, there is a difference in activity between the experimental class students and classroom control, whereas for the students' response to instructional materials as much as 88,79% at SMAN 2, as much as 77,46% at SMAN 4 and as much as 79,74% at SMAN 12 Banjarmasin.Keywords: effectiveness, problem solving, teaching materials, redox reactions